Edexcel International GCSE Chemistry Student Book Second Edition. - Wensley, Robert (Hodder Education Group, 2017)
Exam Board: EdexcelLevel: IGCSESubject: ScienceFirst Teaching: September 2017First Exam: June 2019 Develop your students' scientific thinking and practical skills with this second edition, fully updated to match the new 2017 specifications. - Build students' confidence with in-depth yet accessible scientific content- Test understanding with study questions throughout the book- Prepare students for the exam with sample answers and expert comments plus exam-style questions for every section- Build practical skills with coverage of all required practicals plus further suggested experiments- D.